2012
DOI: 10.1007/s13364-012-0107-8
|View full text |Cite
|
Sign up to set email alerts
|

Habitat correlates of the Eurasian otter Lutra lutra recolonizing Central Poland

Abstract: The increase in Eurasian otter Lutra lutra populations in their natural range and recolonization processes are recently observed in several European countries. We address the process of otter recolonization and habitat utilization in Central Poland over 14 years. Field surveys in 1998 and 2007 documented increase in occurrence of the species. The frequency of positive sites denoted 15 % in 1993, 38 % in 1998, and 89 % in 2007. Otter occurrence at study sites was positively affected by river width while negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 21 publications
0
23
0
4
Order By: Relevance
“…Among the protected mammal species using the crossing structure in Laliki, the otter is also a target species for the neighbouring Natura 2000 sites. This semiaquatic mammal is abundant in the region (Brzeziński et al 1996), and its frequent appearance on the crossing structure might be connected with the presence of the watercourse, as this is its favoured habitat (Romanowski et al 2013). Incorporation of the stream into the design of the wildlife crossing structure might also support the presence of the common polecat and stoat, both of which are associated with aquatic habitats (Jędrzejewska & Jędrzejewski 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Among the protected mammal species using the crossing structure in Laliki, the otter is also a target species for the neighbouring Natura 2000 sites. This semiaquatic mammal is abundant in the region (Brzeziński et al 1996), and its frequent appearance on the crossing structure might be connected with the presence of the watercourse, as this is its favoured habitat (Romanowski et al 2013). Incorporation of the stream into the design of the wildlife crossing structure might also support the presence of the common polecat and stoat, both of which are associated with aquatic habitats (Jędrzejewska & Jędrzejewski 1998).…”
Section: Discussionmentioning
confidence: 99%
“…variables) are combined together by applying a weight to each. The presence of otters has been strongly related to various features of land cover and protected reaches of rivers, and negatively correlated with elevation (Barbosa, Real, Olivero, & Vargas, ; Jo, Won, Fritts, Wallace, & Baccus, ; Robitaille & Laurence, ; Romanowski, Brzeziński, & Żmihorski, ) (see Supporting Information). Four primitive attributes were selected as a basis for development of the habitat suitability mapping: land cover; elevation range; slope; and distance from the river.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have shown that human presence and associated disturbance, even at low levels, may deter river and Eurasian otters from occupying or colonizing various waterways (Prenda et al, 2001;Gaydos et al, 2007;Guertin et al, 2012;Romanowski et al, 2012). For example, Kalz et al (2006) found limited dispersal of Eurasian otters across a highway that bisected a nature reserve in Germany.…”
Section: Discussionmentioning
confidence: 99%